Profile of serum microRNAs in heart failure with reduced and preserved ejection fraction: Correlation with myocardial remodeling - Layde Rosane Paim; Luis Miguel da Silva; Lígia M. Antunes-Correa; Vinicius Citelli Ribeiro; Roberto Schreiber; Eduarda O.Z. Minin; Larissa C.M. Bueno; Elisangela C.P. Lopes; Renan Yamaguti; Andréa Coy-Canguçu; Sergio San Juan Dertkigil; Andrei Sposito; et al. (Heliyon, 2024)
Background and aims: Cardiomyocyte hypertrophy and interstitial fibrosis are key components of myocardial remodeling in Heart Failure (HF) with preserved (HFpEF) or reduced ejection fraction (HFrEF). MicroRNAs (miRNAs) are non-coding, evolutionarily conserved RNA molecules that may offer novel insights into myocardial remodeling. This study aimed to characterize miRNA expression in HFpEF (LVEF ≥ 45%) and HFrEF (LVEF < 45%) and its association with myocardial remodeling. Methods: Prospectively enrolled symptomatic HF patients (HFpEF:n = 36; HFrEF:n = 31) and controls (n = 23) underwent cardiac magnetic resonance imaging with T1-mapping and circulating miRNA expression (OpenArray system). Results: 13 of 188 miRNAs were differentially expressed between HF groups (11 downregulated in HFpEF). Myocardial extracellular volume (ECV) was increased in both HF groups (HFpEF 30 ± 5%; HFrEF 30 ± 3%; controls 26 ± 2%, p < 0.001). miR-128a-3p, linked to cardiac hypertrophy, fibrosis, and dysfunction, correlated positively with ECV in HFpEF (r = 0.60, p = 0.01) and negatively in HFrEF (r = −0.51, p = 0.04). miR-423-5p overexpression, previously associated HF mortality, was inversely associated with LVEF (r = − 0.29, p = 0.04) and intracellular water lifetime (τic) (r = −0.45, p < 0.05) in both HF groups, and with NT-proBNP in HFpEF (r = −0.63, p < 0.01). Conclusions: miRNA expression profiles differed between HF phenotypes. The differential expression and association of miR-128a-3p with ECV may reflect the distinct vascular, interstitial, and cellular etiologies of HF phenotypes.